The overlooked evolutionary dynamics of 16S rRNA revises its role as the "gold standard" for bacterial species identification - Bartoš, Oldřich; Chmel, Martin; Swierczková, Iva (Scientific reports, 2024)
The role of 16S rRNA has been and largely remains crucial for the identification of microbial organisms. Although 16S rRNA could certainly be described as one of the most studied sequences ever, the current view of it remains somewhat ambiguous. While some consider 16S rRNA to be a variable marker with resolution power down to the strain level, others consider them to be living fossils that carry information about the origin of domains of cellular life. We show that 16S rRNA is clearly an evolutionarily very rigid sequence, making it a largely unique and irreplaceable marker, but its applicability beyond the genus level is highly limited. Interestingly, it seems that the evolutionary rigidity is not driven by functional constraints of the sequence (RNA-protein interactions), but rather results from the characteristics of the host organism. Our results suggest that, at least in some lineages, Horizontal Gene Transfer (HGT) within genera plays an important role for the evolutionary non-dynamics (stasis) of 16S rRNA. Such genera exhibit an apparent lack of diversification at the 16S rRNA level in comparison to the rest of a genome. However, why it is limited specifically and solely to 16S rRNA remains enigmatic.
Keywords: Sequence Analysis, DNA; Phylogeny; RNA ribozomální 16S; sekvenční analýza DNA; biologická evoluce; Biological Evolution; fylogeneze; RNA, Ribosomal, 16S